Circulating complement‐1q tumor necrosis factor‐α‐related protein isoform 5 levels are low in type 2 diabetes patients and reduced by dapagliflozin. Issue 1 (6th June 2019) - Zhang, Cheng; Luo, Yong; Liu, Rui; Li, Xiaoqiang; Yang, Mengliu; Zhang, Yu; Li, Ling; Mou, Huaming; Guo, Lian; Li, Jing; Liu, Hua; Yang, Gangyi; et al.
Abstract: Aims/Introduction: As a member of the tumor necrosis factor‐α‐related protein family, complement‐1q tumor necrosis factor‐α‐related protein isoform 5 (CTRP5) has been found to be associated with obesity and insulin resistance (IR). Previous studies in humans and animals have reported contradictory results related to the association between CTRP5 and IR. The purpose of the present study was to explore the relationship between CTRP5 and IR through a cross‐sectional study and drug intervention study of type 2 diabetes patients. Materials and Methods: A cross‐sectional study was carried out with 118 newly diagnosed patients with type 2 diabetes and 116 healthy adults. In an interventional study, 78 individuals with newly diagnosed type 2 diabetes received sodium–glucose cotransporter 2 inhibitor (dapagliflozin) treatment for 3 months. Circulating CTRP5 concentrations were measured by enzyme‐linked immunosorbent assay. Results: Serum CTRP5 concentrations were markedly reduced in patients with type 2 diabetes when compared with those of healthy individuals ( P < 0.01). When considering the study population as a whole, individuals with IR (homeostasis model of assessment of IR ≥2.78) had lower CTRP5 concentrations than the individuals without IR (homeostasis model of assessment of IR <2.78; P < 0.01). Serum CTRP5 negatively correlated with age, body mass index, waist‐to‐hip ratio, Systolic blood pressure, triglyceride, total cholesterol, glycated hemoglobin, fasting blood glucose, 2‐h blood glucose, fasting insulin and homeostasis model of assessment of IR. After 12 weeks of sodium–glucose cotransporter 2 inhibitor treatment, serum CTRP5 levels in type 2 diabetes patients were significantly reduced accompanied with ameliorated glycometabolism and IR compared with before treatment ( P < 0.01). Conclusions: CTRP5 is likely a marker for type 2 diabetes in humans. Abstract : The present study found that complement‐1q tumor necrosis factor‐α‐related protein isoform 5 (CTRP5) levels were reduced in type 2 diabetes patients and that plasma CTRP5 levels were related to insulin resistance. Furthermore, we found that plasma CTRP5 concentrations further decreased after dapaglifozin treatment, which showed that CTRP5 might play an important role in the development of type 2 diabetes.